Management of the ruptured sinus of valsalva aneurysmsa - Gupta, Manju; Shoeb, Mohd; Mishra, Pankaj Kumar; Bathla, Amit; Prasad, Jagdish (International Surgery Journal, 2017)
Background: RSOV is associated with a dramatic onset of symptoms to a state of biventricular failure due to sudden volume overload. Controversies exist about RSOV repairs among various centers are the surgical approach (chamber involved, transaortic or both) and the closure technique (primary/ patch closure). There have been no clinical trials to show that one technique is superior to other. In the present study, we reviewed our 16 years’ experience with repair of RSOV through exclusive transaortic approach. Methods: 40 patients underwent RSOV repair through transaortic approach from January 2000 to December 2016. The mean age was 30.2 years. The origin of RSOV was right coronary sinus in 75% of cases and non-coronary sinus in 22.5% of cases. There was one giant calcified unruptured aneurysm arising from right coronary sinus. Right ventricle was most common chamber of rupture comprising 96.67% cases. All patients underwent transaortic repair of RSOV using dacron patch. VSD repair was done in 25% cases. Aortic valve replacement was done in 62.5% cases for moderate to severe AR. Results: There were 7.5% in hospital deaths with no late deaths. Inotropic and ventilatory support required for 3±1.6 days and 1.8±1.2 days respectively. The mean ICU stay and hospital stay was 3.5±1.6 days and 7.5±2.5 days respectively. None of the patient required permanent pacemaker implantation. The 37 survivors were followed up for 6.4±3.6 years; all had an improvement in functional NYHA class with superior results in those with no aortic regurgitation. 7.5% patients developed mild AR during follow up which medical management was done. Conclusions: Surgical treatment of ruptured sinus of Valsalva aneurysm using the transaortic patch technique has an acceptably low operative risk, lesser distortion of aortic valve and good long-term symptom-freedom survival. An early aggressive approach is recommended to prevent worsening of symptoms and more extensive disease.